2002
DOI: 10.1002/1099-0682(200203)2002:4<876::aid-ejic876>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Isomerisation of Tris(silyl)hydroxylamines to Silylaminodisiloxanes − Experimental and Quantum Chemical Results

Abstract: O‐Lithio‐N,N‐bis(trimethylsilyl)hydroxylamide, LiO−N(SiMe3)2, reacts with ClSiMe2H to give HMe2Si−O−N(SiMe3)2 (1), while LiO−N(SiMe2CMe3)2 reacts with C6H5SiF3 to give C6H5SiF2−O−N(SiMe2CMe3)2 (2). 2 isomerises in solution to give N,O‐bis(tert‐butyldimethylsilyl)‐N‐[difluoro(phenyl)silyl]hydroxylamine (3). Boiling of 1 leads to the structurally isomeric silylaminodisiloxane, Me3Si−O−SiMe2−NH−SiMe3 (4), while boiling of 3 leads to the isomeric Me3CSiMe2−O−Si(Me)CMe3−NMe−SiF2C6H5 (5). Quantum chemical calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
5
10
0
Order By: Relevance
“…It is not self-evident that similar dyotropic rearrangement reactions may take place in hydroxylamines containing germyl or stannyl groups, because these groups are much bulkier than silyl groups so that the acute angles in the corresponding dyotropic transition states are even smaller. It may be anticipated that these transition states are higher in energy than those reported in ref , so that a thermal dyotropic rearrangement is less favorable for stannylhydroxylamines. In this paper we present the synthesis and the X-ray structure of the first N , O -bis(silyl)- N -stannylhydroxylamine.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…It is not self-evident that similar dyotropic rearrangement reactions may take place in hydroxylamines containing germyl or stannyl groups, because these groups are much bulkier than silyl groups so that the acute angles in the corresponding dyotropic transition states are even smaller. It may be anticipated that these transition states are higher in energy than those reported in ref , so that a thermal dyotropic rearrangement is less favorable for stannylhydroxylamines. In this paper we present the synthesis and the X-ray structure of the first N , O -bis(silyl)- N -stannylhydroxylamine.…”
Section: Introductionmentioning
confidence: 71%
“…Attempts to carry out insertion reactions of a dimethylstannyl group or a dimethylsilyl group into the N−O bond under the right reaction conditions, which was successfully done in tris(silyl)hydroxylamine chemistry, , failed until now. In a not transparent, complex reaction we were able to isolate bis(trimethylstannyl)carbodiimide ( 2 ), which was described in 1971, and the dimeric 1,7,9-trisilyl-3,5-distannyl-2,4,6,8-tetraoxane 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that no other class of compounds is comparably rich in isomerization reactions as silylhydroxylamines. Anionic, radicalic, and neutral silyl group migrations and silyl group insertions into the N−O bond have been described. , However, bis(hydroxylamino)silanes have not been isolated so far. Knowing that in contrast to carbon chemistry it is possible to stabilize compounds with two or three electronegative groups such as OH, NH 2 , and PH 2 bonded to one silicon atom, we tried to prepare bis(hydroxylamino)silanes and report our recent results.…”
Section: Introductionmentioning
confidence: 99%